Steady-state heat transit investigation in a radiative cylindrical pipe of reactive materials - Lebelo, Ramoshweu S.; Sibanda, Bonani; Mkhumbeni, Nolutho (Edelweiss Applied Science and Technology, 2025)
This study investigates heat transfer in a combustible material modeled within a cylindrical domain. A combustible material is one that reacts readily with oxygen, such as carbon or hydrocarbons, and the spontaneous reaction it undergoes is called an exothermic chemical reaction. In this context, heat transfer to the environment is assumed to occur via radiation, involving a two-step combustion process in a one-dimensional reaction. The goal of this study is to theoretically demonstrate how heat is transferred from reactive materials through an exothermic chemical reaction mechanism to the surrounding environment, using a mathematical approach. This method is faster and more cost-effective than experimental procedures. It involves solving the nonlinear ordinary differential equation governing the process by coupling the fourth-order Runge-Kutta (RK45) numerical method with the Shooting Technique. The heat transfer process is influenced by various thermo-physical parameters that affect the system’s temperature during combustion. Results show that kinetic variables, such as the Frank-Kamenetskii parameter, also known as the reaction rate, enhance the combustion process, while factors like radiation retard it. An understanding of the heat transfer of reactive materials is crucial in manufacturing industrial equipment to ensure quality and safety.